Pengaruh Pendekatan Pendidikan Matematika Realistik terhadap Kemampuan Komunikasi Matematis Siswa Kelas VII SMP - Yunisha, Rizqa; Prahmana, Rully Charitas Indra; Sukmawati, Klara Iswara (Universitas Hamzanwadi, 2016)
This research is motivated by the low mathematical communicating skills of junior high school students. The aim of this study is to know the differences in average score of mathematical communicating skills between the students once learnt using realistic mathematics education approach and students learnt using conventional approach. This research used a quasi-experimental method with non-equivalent control group design. The population used were all 7th grade students in SMP Negeri 2 Pagedangan, with two classes used as samples. This research datas are obtained from studentsâ scores in pretest and posttest. Based on the analysis of the research results, it is concluded that there are differences in the average score of matematical communicating skills between the students once learnt using realistic mathematics eduacation approach and conventional approach. The average score of mathematical communicating skills of the students learnt using realistic mathematics education approach is higher than the students learnt using conventional approach.